2017
DOI: 10.1083/jcb.201701047
|View full text |Cite
|
Sign up to set email alerts
|

The spread of prion-like proteins by lysosomes and tunneling nanotubes: Implications for neurodegenerative diseases

Abstract: Victoria and Zurzolo discuss current evidence for the emerging role of lysosomal damage and tunneling nanotubes in the intercellular propagation of prion and prion-like proteins in neurodegenerative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
118
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 142 publications
3
118
0
2
Order By: Relevance
“…Of interest, TNTs can mediate the transfer of infectious prion particles (Gousset et al, 2009) and other prion-like proteins (Victoria & Zurzolo, 2017). Specifically, we have shown that fibrils of a-synuclein (a-syn), a prion-like protein involved in Parkinson's disease (PD) pathology, can be transferred between neuronal cells (CAD cells) in culture through TNTs (Abounit et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, TNTs can mediate the transfer of infectious prion particles (Gousset et al, 2009) and other prion-like proteins (Victoria & Zurzolo, 2017). Specifically, we have shown that fibrils of a-synuclein (a-syn), a prion-like protein involved in Parkinson's disease (PD) pathology, can be transferred between neuronal cells (CAD cells) in culture through TNTs (Abounit et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, it was recently reported that the intracellular pool is mainly formed from aggregation-prone, toxic Aβ42, while the less toxic Aβ40 is more abundant extracellularly (Sannerud et al, 2016). Intracellular accumulation of amyloidogenic proteins causes decreased lysosomal efficiency, detected as reduced capacity of degradation, abnormal lysosomal morphology and lysosomal membrane permeabilization as hallmark of neurodegenerative diseases (Freeman et al, 2013;Eriksson et al, 2017;Victoria and Zurzolo, 2017;Gowrishankar et al, 2015). Lysosomes are central hubs for nutrient homeostasis but are also actively involved in cell death induction and PM repair.…”
Section: Oaβ Propagation To Healthy Cells Is Mediated By Transport Inmentioning
confidence: 99%
“…Recently, several studies have demonstrated TNTs to transfer neurodegenerative proteins, such as PrP Sc , α-synuclein, Aβ, tau, polyQ, directly from one cell-to-another (Gousset et al, 2009;Wang et al, 2011;Zhu et al, 2015;Tardivel et al, 2016;Dieriks et al, 2017). Several of these studies implicated links between TNTs and the endo-lysosomal pathway in cell-to-cell spreading (Bhat et al, 2018;Victoria and Zurzolo, 2017). These studies and the discovery of TNTs (Rustom et al, 2004) TNTs are open ended membrane nano-structures with membrane actin protrusions between neighbouring cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other types of neurodegenerative diseases, the infectious and seeding ability is the most distinguishable feature of the Prion disease, which enables the spreading of misfolded prion proteins from peripheral regions to the central nervous system and even interspecies transmissibility (Victoria & Zurzolo, 2017). …”
Section: Introductionmentioning
confidence: 99%